Nutritional and blood pressure screening in school children in rural South India: a cross-sectional study - Roy, Dhanya; Singh, Sundar; Joseph, Lenikumar (International Journal of Contemporary Pediatrics, 2021)
Background: Screening for diseases is not very popular in Indian populace in general, and receive little attention from heath care policy makers, administrators or even health care providers, who concentrate on curative services. Health and nutritional screening of school children and adolescents, remains virtually a neglected field. So we conceived this study to look at the feasibility of large scale health screening of adolescents at school by a simple and inexpensive way by looking into the nutritional status (survey of anthropometry) and blood pressure readings among adolescents. Methods: Students from 5 rural school in South India from age group of 10 to 18 years (fifth to twelfth standard) were assessed for their height, weight, BMI and blood pressure. Data was entered in WHO EpidataTM (version 3.0) and transferred to SPSS 12.0 version for analytical studies. Results: In current study of 2201 students, wasting (35.5%), stunting (24.5%), high BMI (7.6%) were found. Prevalence of wasting is 1.63 times higher in males (p<0.001). There is significant relationship with high BMI and severe stunting (p<0.001, OR 2.54; 1.58%, 4.1%; 95% CI). Prevalence of pre-hypertension is 14.1% and hypertension is 9.5%. There is a linear trend in the prevalence of hypertension and BMI (p<0.001). As the BMI increases, blood pressure also increases. Conclusions: Even with all advances in health care, undernutrition is highly prevalent. Obesity is on a rise in rural population and high proportions of overweight children are stunted also. High BMI is a risk factor for hypertension.